Pots, symbols and territories: the archaeological context of neolithisation in Mediterranean Spain - Bernabeu Aubán, Joan (Documenta Praehistorica, 1999)
The central idea in this paper is that the spread of agriculture within the Iberian Peninsula resulted from both a kind of demic spread and the acculturation of the Mesolithic substratum. The suggestion of the dual model presented earlier (Bernabeu 1996; 1998) emphasises precisely this aspect and its consequence: the existence of a certani regional diversity in the processes of agricultural distribution. Within this context, it is suggestend that the variability asociated with decorative patterns and styles of impressed pottery and rock art has a clear territorial component. The spread of these symbolic manifestations can be better understood in the context of the interaction between farmers and hunters, and by assuming that assimilationwas not the only result of this interaction process.
Keywords: archaeology; arheologija; arheološke najdbe; ceramic; keramika; kolonizacija; Spain; Španija